An unusual presentation of rectal atresia with rectal duplication cyst in a neonate: A case report (Indian Journal of Case Reports, 2015)
A 10 days old male baby brought with abdominal distension and cystic swelling in the left buttock. Radiological investigations suggested para-rectal abscess or rectal duplication cyst. Patient underwent transverse loop colostomy and later definitive surgery by posterior sagittal approach. Intra-operative findings were suggestive of small atretic rectal segment with duplication cyst of the rectum. To the best of our knowledge, neonatal rectal atresia with rectal duplication cyst has not been reported in English literature.